Innovation ecosystem as a new form of organizational integrity and a mechanism for financing and reproducing innovations - I. A. Ezangina; A. E. Malovichko; A. A. Khryseva (Финансы: теория и практика, 2023)
The subject of the study is the factors, models and processes of the emergence and development of modern innovation ecosystems (IES) that ensure the flow of assets, their transformation into innovations, and distribution across the territories of economic growth. The purpose of the paper is to identify the factors and trends in the development of the IES, based on the practices of individual States and driving forces of the world. The methods of sampling, grouping, comparison, analogy, analysis, generalization, system-structural approach to assessing the development of the subject of research are used. The result of the study was the definition of IES as an open institutional mechanism for the reproduction of innovations, transforming the competitive market environment in the direction of the dominance of stable intersectoral network structures. The decisive role of IES in the chain “national innovation strategy → (start-ups + companies + state institutions) → IES → [new start-ups + deep-tech companies unicorns (hectocorns) + new level of quality of the competitive environment] → global competitive advantage of the State” is established. On the example of China, the prospects of formation a model of the national IES, focused on long-term development, technological selfsufficiency of the State and, at the same time, providing the possibility of expansion to new markets, are proved. The authors see the prospects for further research of the IES in Russia in a shift of emphasis from the “banking” nature of the IES towards the formation of large territorial centers of the location of the IES while maintaining strong institutional support of the State.